Lactoferrin Retargets Human Adenoviruses to TLR4 to Induce an Abortive NLRP3-Associated Pyroptotic Response in Human Phagocytes - Chéneau, Coraline; Eichholz, Karsten; Tran, Tuan Hiep; Tran, Thi Thu Phuong; Paris, Océane; Henriquet, Corinne; Bajramovic, Jeffrey J.; Pugniere, Martine; Kremer, Eric J. (Frontiers in Immunology, 2021)
Despite decades of clinical and preclinical investigations, we still poorly grasp our innate immune response to human adenoviruses (HAdVs) and their vectors. In this study, we explored the impact of lactoferrin on three HAdV types that are being used as vectors for vaccines. Lactoferrin is a secreted globular glycoprotein that influences direct and indirect innate immune response against a range of pathogens following a breach in tissue homeostasis. The mechanism by which lactoferrin complexes increases HAdV uptake and induce maturation of human phagocytes is unknown. We show that lactoferrin redirects HAdV types from species B, C, and D to Toll-like receptor 4 (TLR4) cell surface complexes. TLR4-mediated internalization of the HAdV-lactoferrin complex induced an NLRP3-associated response that consisted of cytokine release and transient disruption of plasma membrane integrity, without causing cell death. These data impact our understanding of HAdV immunogenicity and may provide ways to increase the efficacy of HAdV-based vectors/vaccines.